Nilai Sosial dan Nilai Religius Novel 40 Hari Takdir Itu Bernama Hidup dan Mati - Lailatul Rhomadania; Siti Jamila; Siti Fatimah; Ahmad Ilzamul Hikam (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to identify the representation and manifestation of social values contained in the novel “40 Hari Takdir Itu Bernama Hidup dan Mati” (40 Days of Destiny Called Life and Death) by Adeicama. The research method used is a literature study with note-taking techniques on primary data (novels) and secondary data (related literature). Data analysis was conducted using descriptive qualitative methods based on Wirawan's theory of social values, Mulyana's theory of religious values, and Nurgiyantoro's theory of literary analysis. The results show that this novel represents social values through solidarity, caring, responsibility, and criticism of technological dependence. Religious values are manifested through faith in destiny, sincerity in loss, self-control, and the role of prayer and hope. These two aspects of value are interrelated, enriching the meaning of the story and providing an understanding of how humans deal with the uncertainties of life through social norms and spiritual strength. This research contributes to the development of literary studies and literary sociology, and is relevant for increasing public appreciation and critical understanding of the function of literature as a reflection of ethical and social norms.